IMPLANTATION: INSIGHT TO THE EFFECTS OF CYTOKINES AND GROWTH FACTORS - Sinawat, Supat (Srinagarind Medical Journal, 2013)
Introduction Implantation is the process of which the blastocyst attaches to the uterine epithelium. Generally there are two factors which determine the success of implantation. These include (1) the production of the hatched blastocyst capable of implanting and (2) the development of an endometrium that is receptive to the embryo. Overall responsibilities for the coordination of these two processes lies with ovarian hormones, estrogen and progesterone. However, it is now clear that under their influence, locally acting soluble factors secreted by the endometrium can act on the embryo to influence its development. Developing embryos, in turn, have been shown to produce soluble factors, cytokines and growth factors, that can act in an autocrine manner, or on the endometrium to influence receptivity (1, 2) . This article will review new data indicating a critical role for cytokines and growth factors, both in preimplantation embryo development and endometrial receptivity.